Ultrasound-Guided Combined Interscalene-Cervical Plexus Block for Surgical Anesthesia in Clavicular Fractures: A Retrospective Observational Study - Onur Balaban; Turan Cihan Dülgeroğlu; Tayfun Aydın (Anesthesiology Research and Practice)
Objective. We aim to report our experiences regarding the implementation of the ultrasound-guided combined interscalene-cervical plexus block (CISCB) technique as a sole anesthesia method in clavicular fracture repair surgery. Materials and Methods. Charts of patients, who underwent clavicular fracture surgery through this technique, were reviewed retrospectively. We used an in-plane ultrasound-guided single-insertion, double-injection combined interscalene-cervical plexus block technique. During the performance of each block, the block areas were visualized by using a linear transducer, and the needles were advanced by using the in-plane technique. Block success and complication rates were evaluated. Results and Discussion. 12 patients underwent clavicular fracture surgery. Surgical regional anesthesia was achieved in 100% of blocks. None of the patients necessitated conversion to general anesthesia during surgery. There were no occurrences of acute complications. Conclusions. The ultrasound-guided combined interscalene-cervical plexus block was a successful and effective regional anesthesia method in clavicular fracture repair. Prospective comparative studies would report the superiority of the regional technique over general anesthesia.